Takhrij and Syarah Hadith of Chemistry: Argumentation of Chemistry to Audience Doubt about Hadith of â€œIf Flies Land on The Vesselâ€ - Fauziah Muthi Millatina; Saila Salsabila; Rosihon Anwar; Wahyudin Darmalaksana; Asep Supriadin (UIN Sunan Gunung Djati Bandung, 2021)
This research aims to discuss the hadith of the Prophet Muhamammad SAW. about flies if land on a beverage. This research method is qualitative through the approach of takhrij and syarah hadith with chemical analysis. The results and discussion of this research are hadith about the flies land on the vessel becomes controversy among the public, however a research can prove that submerging flies into vessels can produce positive results. The conclusion of this research is that the hadith has shahih quality and can be proven the truth of the contents of the hadith, that with chemical analysis the flies have right and left wings with different functions.